Written Corrective Feedback in Academic Writing Class: How Does Experienced Teacher Lead the Effective Practice? - Dayat Dayat (Edukasi: Jurnal Pendidikan, 2021)
AbstractThe research aimed to investigate an Indonesian academic writing teacher’s practice on written corrective feedback (WCF) in academic writing class. A case study involving an experienced Indonesian academic writing teacher and teacher students were employed. To gather data, a semi-structured interview was conducted. The data were then analyzed using the content analysis method. The findings indicated that the teacher’s practice on WCF was mediated by her language learning experience. Thus, the teacher provided WCF on her students’ writing drafts by considering the students’ personalities and their level of writing ability. In correcting student writing errors, the teacher used several types of WCF; direct and indirect correction; metalinguistic clues to the errors; and the reformulation of the wrong words. The relevant pedagogical implications for teachers in conceptualizing WCF and in learning and practicing it on their daily instruction based on their knowledge, experience, and reflection-on-practice. AbstrakPenelitian bertujuan untuk mendeskripsikan praktik dosen Indonesia dalam penulisan akademik tentang umpan balik korektif tertulis (WCF) di kelas penulisan akademik. Penelitian termasuk studi kasus yang melibatkan seorang dosen Indonesia dalam menulis akademik yang berpengalaman dan mahasiswa. Untuk mengumpulkan data, dilakukan wawancara semi-terstruktur. Data tersebut kemudian dianalisis dengan menggunakan metode analisis isi. Temuan menunjukkan bahwa praktik dosen pada WCF dimediasi oleh pengalaman belajar bahasanya. Dosen memberikan WCF pada draf tulisan mahasiswanya dengan mempertimbangkan kepribadian mahasiswa dan tingkat kemampuan menulisnya. Dalam mengoreksi kesalahan menulis mahasiswa, dosen menggunakan beberapa jenis WCF; koreksi langsung dan tidak langsung; petunjuk kesalahan metalinguistik; dan perumusan ulang kata yang salah. Implikasi pedagogis yang relevan bagi dosen dalam membuat konsep WCF dan dalam mempelajari serta mempraktikkannya pada instruksi harian berdasarkan pada pengetahuan, pengalaman, dan refleksi pada praktik yang dilaksanakan.